ANALYSIS OF THE NEED FOR TEACHING MATERIALS FOR SOIL MEASUREMENT II - Riyan Arthur; Prihantono; Salma Maharani; Dendy Wahyu Kuntoro (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to obtain information about problems in the learning process of the Land Surveying course in S1 majoring in Building Engineering Education, State University of Jakarta.The study was conducted in April to May 2019 with a data collection method in the form of a questionnaire / questionnaire with a simple random sampling technique consisting of 44 respondent students majoring in S1 Engineering Education Building in Jakarta State University. The results of the needs analysis show that; 86% of respondents have difficulty in learning materials contained in other sources due to incomplete material, explanatory techniques that are difficult to understand and others; 61% of respondents answered that they were not able to apply the material during the practicum after studying the Land Surveying II course from various sources they studied. In general, the results of this needs analysis can be used as a guideline in the design of teaching materials for Land Surveying II.